Public speaking anxiety level of grade 11 learners at Santo Tomas Catholic School : basis for an intervention material - Biswayan, Jonalyn R. (Pangasinan : [s.n.], 2017)
The study analyzed the public speaking anxiety (PSA) level among the 111 Grade 11 learners of Santo tomas Catholic School. Survey quesationnaire supported and verified the information gathered. The study used descriptive research design. To substantiate the questions, a pre-test was conducted in a form of impromptu speech. Right after the delivery, two questionnaires were given to be answered immediately. These were the personal report of Public Speaking Anxiety developed by McCroskey (1970) and the Demographic Profile questionnaire. To determine the learners' PSA level, the weighted means of the ratings were interpreted based on a 5-point scale. The Pearson r was used in order to identify the relationship of the profile and the PSA level of respondents.
Bibliography: pages 100-104.
CHED-La Union
Keywords: Public speaking